2008
DOI: 10.1029/2007jb005574
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for ground motion polarization on fault zones of Mount Etna volcano

Abstract: [1] During local and regional earthquakes, an evident amplification of horizontal ground motion is observed at two seismological stations near the Tremestieri fault, on the southeastern flank of Mount Etna volcano. Rotated component spectral ratios show a narrow spectral peak around 4 Hz along a N40°E direction. A conventional polarization analysis using the eigenvectors of the covariance matrix confirms the very stable directional effect enhancing the approximately NE-SW elongation of the horizontal ground mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 41 publications
7
36
2
Order By: Relevance
“…The azimuth pattern of HVSR complements the rose diagrams giving (1) clear indication of the frequencies where directional effects occur, and (2) the level of horizontal ground motion compared to the vertical one. As found by Rigano et al [2008] at Mount Etna, the directions inferred from the azimuth pattern of HVSR are consistent with those provided by the covariance matrix method.…”
Section: Array Experiments Tremor Measurements and Analysis Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…The azimuth pattern of HVSR complements the rose diagrams giving (1) clear indication of the frequencies where directional effects occur, and (2) the level of horizontal ground motion compared to the vertical one. As found by Rigano et al [2008] at Mount Etna, the directions inferred from the azimuth pattern of HVSR are consistent with those provided by the covariance matrix method.…”
Section: Array Experiments Tremor Measurements and Analysis Methodssupporting
confidence: 84%
“…Results of conventional covariance matrix analysis are also shown in Figure 6 as rose diagrams. The polarization vector at each station was measured by diagonalizing the covariance matrix using the technique already adopted by Rigano et al [2008]. It moves a time window of 2 s with a 50% partial overlap throughout the entire tremor record of each site (the same used for the computation of HVSR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Biondi and Maugeri (2005), Lombardo et al (2004Lombardo et al ( , 2006, Catalano et al (2005), Lombardo and Rigano (2007) evaluated the local seismic response in test sectors of the urban area, whereas preliminary estimates of site response in the whole Catania area were obtained by Giampiccolo et al (2001), Lombardo et al (2001), Priolo et al (2005). Further investigations on the local effects due to fault zones (Rigano et al 2008) as well as natural cavities Lanzo et al 2006;Sgarlato et al 2009) have been recently performed and others are still in progress.…”
Section: Forewordsmentioning
confidence: 96%
“…In Figure 3, some examples of polarization plots obtained by Rigano et al (2008), from microtremor measurements performed along and across the Pernicana and Tremestieri faults, are reported. The authors analyzed both earthquake and ambient noise records and found that in all investigated sites the ground motion polarization azimuths were principally NW-SE and NE-SW oriented, for the Pernicana (Fig.…”
Section: Resultsmentioning
confidence: 99%